EVALUATION AND DEVELOPMENT OF THE TEACHING MODULE OF SPEAKING 1 - Sri Endah Kusmartini; Risnawati _; Risa -; Darmaliana _ (Politeknik Negeri Sriwijaya, 2017)
In the hospitality industry, English speaking competence is needed in order to be able to compete in this global era. The assignment of the people in an educational institution is to ensure that the students have the teaching module to study. The main objective of this study was to evaluate and develop the teaching Module of Speaking 1. It was a research and development study. The research was conducted in English Department Sriwijaya State Polytechnic. The research applied small-scale project of R & D developed by Gall, Borg, and Gall (2003). The research revealed that based on the evaluation, the existing Speaking 1 module produced in 2014 was not appropriate anymore and needed to be developed. Therefore, lesson plan was designed based on the newest syllabus. The teaching module of Speaking 1 was developed based on the lesson plan. Content validation and construct validation were conducted to the draft. Main product revision was conducted based on the content and construct validation. Main field testing was conducted to see the practicality and the level of difficulties of the draft. The final revision was conducted based on the main field testing. This small-scale project of R & D cycle was conducted due to time and budget limitation.